Assessment of iodine deficiency disorder among school going children aged 5-10 years in Sagar district of Madhya Pradesh: an observational cross sectional study - Jain, Arpita; Verma, Shipra; Toppo, Manju; Nair, Akhil R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Iodine deficiency (IDD) is the world’s most prevalent cause of brain damage. glaciations, flooding, rivers lead to deficiency of iodine in crops grown on iodine. Diet low in iodine can result in stillbirth and abortions and many more sequelae. Objectives of the research work were to study the prevalence of IDD amongst 6-12 years children by clinical examination and to determine the concentration of iodine in salt sample at consumer level. Also, to determine the urinary iodine excretion amongst 6-12 years age group children. Methods: It was a cross sectional study conducted in the government schools of Sagar district among school children of 6-12 years of age. Total 2700 school children from 30 villages were included using PPS sampling. Students were clinically examined and their urine samples were taken for MUIC estimation. Results: Prevalence of goiter was more in 10 to 11 years of age (14.07%) and less in 8 to 9 years age group (7.59%). Overall prevalence of goiter in district Sagar is 10.51%. Conclusions: Despite NIDDCP, there is still dearth of awareness among general public about the usage and storage of iodized salt which is the root cause of Iodine deficiency.